The Predicament of the Tunisian Economy, the Slow-Down in Factors' Productivity - Bernard, Alain; Lafi, Mosbah (Technium Social Sciences Journal, 2021)
Several studies and the mere examination of data provided by National Accounts point to a severe downward change in the economic growth of the Tunisian economy, mainly in the manufacturing sector. The aim of the paper is to perform econometric estimations of the production function, at the aggregate level and for the main sectors and sub-sectors to exhibit a possible change in the global productivity of factors of production, labor and capital. Near-evenly, i.e. with the exception of few sectors or sub-sectors, the breakdown starts from 2013 and various factors, economic and political, may explain it. The topic of the paper is to measure it, not to give explanations. What is at stake is the economic interpretation, either a downturn in the productivity of factors, or a decrease in their utilization. Answering to this question is not easy because there does not exist any survey on the rate of utilization of factors, though indirect methods can be contemplated. This issue, and the related one of the marginal productivity of capital, remain to be assessed.